Growth without Governance - Kaufmann, Daniel; Kraay, Aart (World Bank, Washington, DC, 2014)
It is well known that there is a strong positive correlation between per capita incomes and the quality of governance across countries. the authors propose an empirical strategy that allows separation of this correlation into (1) a strong positive causal effect running from better governance to higher per capita incomes, and, perhaps surprisingly at first, (2) a weak and even negative causal effect running in the opposite direction from per capita incomes to governance. The first result confirms existing evidence on the importance of good governance for economic development. The second result is new and suggests the absence of a "virtuous circle" in which higher incomes lead to further improvements in governance. This motivates the authors' choice of title, "Growth Without Governance." They document this evidence using a newly updated set of worldwide governance-indicators covering 175 countries for the period 2000-01, and use the results to interpret the relationship between incomes and governance focusing on the Latin America and Caribbean region-within a worldwide empirical context. Finally, the authors speculate about the potential importance of elite influence and state capture in accounting for the surprising negative effects of per capita incomes on governance, present some evidence on such capture in some Latin American countries, and suggest priorities for actions to improve governance when such pernicious elite influence shapes public policy.